Performance of adjunctive test and screens in the diagnosis of neonatal sepsis [YENIDOGAN SEPSIS TANISINDA KULLANILAN NON-SPESIFIK YARDIMCI TANISAL TESTLERIN KARSILASTIRILMASI] - (:unkn) unknown (My University, 1996)
Accurate diagnosis of neonatal sepsis is a difficult task for the clinician. A comprehensive diagnostic and management evaluation using risk factors, clinical symptoms and signs, specific definitive diagnostic tests and adjunctive screening tests offers the most rational approach to this problem. In this study we report the performance of adjunctive tests and screens in the diagnosis of neonatal sepsis.